The first Portuguese Textbooks of the German Language, based on the Method Gaspey-Otto-Sauer - Kemmler, Rolf (Revista da ABRALIN, 2021)
In addition to other works designed to support the acquisition of modern foreign languages from the second half of the nineteenth century onwards, the so-called 'conversation grammars' and 'elementary grammars' of the Heidelberg Julius Groos Verlag occupy a central position in the teaching concept of this publishing house, which is still referred to today as the Method Gaspey-Otto-Sauer (MGOS). This paper explores the relationship between a contemporary edition of the French language conversation grammar Nouvelle grammaire allemande (1882) and the first edition of the Portuguese language Nova grammatica allemã theorica e pratica (1887), as well as the elementary grammars Petite grammaire allemande (1881) and Grammatica elementar allemã: adaptada á lingua portugueza (1887). In particular, this paper examines how the editor or author José Prévôt (fl. 1887) proceeded in preparing the editions for which he ultimately assumed responsibility